Handy Enterprise : Working Glove For Construction / Dhaniyah Aimi Darul Amin ...[et al.] - Darul Amin, Dhaniyah Aimi; Jasmi@Jasni, Fadlin Afifa; Jamalludin, Fatin Afifah Nadira; Saiful Amri, Fatin Hamimi; Nor Akmal, Fatin Nabilah (2017)
Our working glove is for construction working that is convenience for every construction workers. This glove is very rare because it is made from Kevlar Cut Resistance that is a very strong fiber and long lasting. Handy Enterprise is a company which is selling high quality handmade glove in Johor. This glove is needed for every construction place in Johor as Johor is one place where all the buildings are rises and many constructions. The glove is made in standard size which is can fit with any hands. Our glove colour is consist two colours, yellow and blue. We sell and supply the glove at supermarket, hardware stores, contractor company and shopping mall. Our price is also affordable and nice to supply especially for contractor company. Based on the objectives above, we are involve in supplying glove in many places. This glove has the potential for being a profitable business if it is done in modern way with systematically managed. We will aspect our business will become more developed in the near future because it is the new innovation in glove. This will give advantage for us to make our product stable in the long run.